PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN STRUKTUR GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Zulhelmy M. Hatta; Lidia Zareva (UIR Press, 2017)
This study aims to determine the effect of financial performance on corporate value which in this case is measured using the disclosure of corporate social responsibility, dependent commissioner, and institutional ownership as a moderating variable. Population in this research is Consumer Goods Industry company listed in Indonesia Stock Exchange during observation period year 2010-2012. Sample selection is done based on purposive sampling method with the aim to get the samples according to the purpose of research. Samples were taken as many as 21 companies with 63 samples from 2010 to 2012. The result of the research is ROA has significant effect to Tobins'Q with a significant probability of 0.000. While the analysis of moderating variables with MRA method known that CSR Disclosure is able to influence the relationship between ROA with Tobins'Q, Independent Commissioner is also able to influence the relationship between ROA with Tobins'Q and Institutional Ownership able to influence the relationship between ROA with Tobins'Q.